2015
DOI: 10.1097/md.0000000000001701
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Comparison of 18F-fluorocholine PET/CT, Ultrasonography and 123I/99mTc-sestaMIBI Dual-Phase Dual-Isotope Scintigraphy in the Preoperative Localization of Hyperfunctioning Parathyroid Glands in Primary or Secondary Hyperparathyroidism

Abstract: We compared 18F-fluorocholine hybrid positron emission tomography/X-ray computed tomography (FCH-PET/CT) with ultrasonography (US) and scintigraphy in patients with hyperparathyroidism and discordant, or equivocal results of US and 123I/99mTc-sesta-methoxyisobutylisonitrile (sestaMIBI) dual-phase parathyroid scintigraphy. FCH-PET/CT was performed in 17 patients with primary (n = 11) lithium induced (n = 1) or secondary hyperparathyroidism (1 dialyzed, 4 renal-transplanted).The reference standard was based on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
164
0
19

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(194 citation statements)
references
References 39 publications
11
164
0
19
Order By: Relevance
“…30 Interestingly, recent studies have shown that 18 F-fluorocholine positron emission tomography (PET) is a very promising imaging method for localization of parathyroid adenomas. [31][32][33][34][35][36] Our results are in agreement with these observations and could represent the biologic substrate and justification to the use of 18 F-fluorocholine PET imaging in HPT. Moreover, a higher amount of succinate and fumarate was shown by network analysis within SGD compared with MGD, suggesting an increased activity of the tricarboxylic acid cycle.…”
Section: Discussionsupporting
confidence: 81%
“…30 Interestingly, recent studies have shown that 18 F-fluorocholine positron emission tomography (PET) is a very promising imaging method for localization of parathyroid adenomas. [31][32][33][34][35][36] Our results are in agreement with these observations and could represent the biologic substrate and justification to the use of 18 F-fluorocholine PET imaging in HPT. Moreover, a higher amount of succinate and fumarate was shown by network analysis within SGD compared with MGD, suggesting an increased activity of the tricarboxylic acid cycle.…”
Section: Discussionsupporting
confidence: 81%
“…Five recent studies published results regarding 18F-FCH; however, Michaud et al and Lezaic et al published two articles using the same population [28, 29, 37, 38]. The most recent study of Michaud et al included 17 patients without prior neck surgery, divided in 11 patients with pHPT, five with sHPT, and one lithium-associated [28].…”
Section: Resultsmentioning
confidence: 99%
“…The most recent study of Michaud et al included 17 patients without prior neck surgery, divided in 11 patients with pHPT, five with sHPT, and one lithium-associated [28]. All patients had 18F-FCH PET-CT because of negative/discordant ultrasound and 123 I/ 99m Tc-sestamibi subtraction scintigraphy.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, being the experience with radiolabeled choline PET/CT largely linked to studies developed on PC patients, few information are available on its "in vivo" bio-distribution in female patients. In fact, this radiopharmaceutical was administered in female patients only in few papers investigating parathyroid adenomas (24) or BT (25). As a matter of fact, in these last cited papers, the acquisition protocols were developed with segmental scans of brain and/or neck, not including the rest of the female body.…”
Section: Introductionmentioning
confidence: 99%